Pengembangan Video Pembelajaran Berbasis Literasi Sains Materi Organ Pencernaan Manusia dan Fungsinya Siswa Kelas VB Sekolah Dasar Negeri 58 Sungai Raya - Novi Indriani; Siti Halidjah; Hery Kresnadi (Departement of Mathematics Education, 2024)
This study aims to analyze the level of validity and practicality of learning videos based on scientific literacy on the material of the human digestive organs and their functions for class V Elementary School. The research method used is research and development (RnD) by adopting the Borg and Gall model with potential and problem steps, data collection, product design, design validation, design revision, product testing, and product revision. Quantitative data were obtained from the results of product assessments by the validator, the results of filling out the practicality questionnaire on videos by teachers and students. Qualitative data were obtained from suggestions or comments by validators, teachers and students. The research instrument is a questionnaire. The validity level of the video is based on the results of assessments by media experts and material experts while the practicality level of the video is based on the results of responses by teachers and students. The results of the validation level of scientific literacy-based learning videos on the material of the human digestive organs and their functions for class V Elementary School by media experts obtained an average of 4.06 in the